A new class of promising biodegradable kinetic/anti-agglomerant methane hydrate inhibitors based on castor oil. (12th October 2019) - Farhadian, Abdolreza; Varfolomeev, Mikhail A.; Kudbanov, Arman; Gallyamova, Svetlana R.
Graphical abstract: Highlights: A new type of kinetic/anti-agglomerant methane hydrate inhibitors was proposed. They were synthesized by simple way from castor oil using waterborne technique. Synthesized castor oil based waterborne poly urea/urethanes (CWPUUs) are biodegradable. CWPUUs significantly increase the induction time and decrease the temperature of methane hydrate formation. CWPUUs prevent gas hydrate growth and aggregation. Abstract: This study is devoted to the evaluation of vegetable oils (in this case castor oil) as an inexpensive, sustainable, environment-friendly, natural and promising resource to design/synthesis efficient kinetic/anti-agglomerant methane hydrate inhibitors. The castor-based waterborne polyurea/urethanes (CWPUUs) were synthesized on the basis of the waterborne technique. The high-pressure autoclave cell and high-pressure micro-differential scanning calorimeter (HP-μDSC) using methane gas were applied to evaluate the inhibition performance of CWPUUs as an inhibitor for methane gas hydrate formation. The results of gas uptake tests confirm that the CWPUUs show high efficiency as kinetic hydrate inhibitors (KHIs). The CWPUUs with ∼3.2 and 6.8 kD molecular weight delayed the onset time of methane hydrate formation by a factor of 26.8 and 13 times and reduced the methane hydrate growth rate by a factor of 3.8 and 2.5 times in comparison with pure water. The results were further confirmed through DSC measurements, in which the usage of CWPUUs with ∼3.2 and 6.8 kD molecular weight decreased the mean onset temperature of methane hydrate formation on 6.1 and 4.7 °C compared to pure water, respectively. Additives of CWPUUs (1 wt % solution) increased the mean onset time of methane hydrate formation from 2.3 h for pure water to 8.7 and 6.4 h. CWPUUs also demonstrated the thermodynamic inhibition by decreasing the melting temperature of methane hydrates comparing to the pure water system. On the other hand, the torque measurements were used to assess anti-agglomerant performance of CWPUUs. During the methane hydrate formation in the presence of CWPUUs, the torque changes remained constant that suggests the hydrate particles stayed separate without aggregation. Moreover, synthesized CWPUUs can be related to biodegradable substances because their BOD5 /CODcr value measured in this work is equal to 0.389. Hence, the application of CWPPUs can be a prospective option for delaying the onset time/temperature of hydrate formation, reducing hydrate growth rate and preventing agglomeration of hydrate particles, and this strategy refers to the terms of green chemistry.